2014
DOI: 10.5799/ahinjs.01.2014.01.0358
|View full text |Cite
|
Sign up to set email alerts
|

Can lactoferrin modulate the immunostimulant activity of levamisole in rats immunosuppressed by cyclophosphamide?

Abstract: ÖZETAmaç: Bu çalışmanın amacı immunsuprese rat modelinde laktoferrin kullanılarak levamizolün immün düzenleyici aktivitesini araştırmaktır.Yöntemler: Çalışma planı: Çalışmada 14 haftalık 140 erkek albino rat (250-280 g) kullanıldı. Ratlar herbirinde 20 rat bulunan 7 gruba ayrıldı. Birinci grup Kontrol grubu, Grup II'ye siklofosfamid tek intraperitoneal dozda (250 mg), Grup III siklofosfamid ve laktoferrin verilen grup, Grup IV oral içme suyu içinde sadece Laktoferrin (%0,5) verilen grup; Grup V siklofosfamid v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…This study shows similar results compared to the data we have obtained in our study. In another study, it was observed that there was no significant difference in total protein, α-and β-globulin levels in oral drinking water administration of lactoferrin (0.5%), but a significant increase (P<0.001) in albumin levels in rats (Mohamed, 2014). Similarly, in this study, it was found that serum albumin, total protein and globulin levels in rats did not change through lactoferrin administration compared to control.…”
Section: Groupssupporting
confidence: 56%
“…This study shows similar results compared to the data we have obtained in our study. In another study, it was observed that there was no significant difference in total protein, α-and β-globulin levels in oral drinking water administration of lactoferrin (0.5%), but a significant increase (P<0.001) in albumin levels in rats (Mohamed, 2014). Similarly, in this study, it was found that serum albumin, total protein and globulin levels in rats did not change through lactoferrin administration compared to control.…”
Section: Groupssupporting
confidence: 56%
“…Therefore, it can be used as a drug that can cause a measurable immunеdeficiency state (Akhter et. al., 2008;Ukpo, 2013;Mohamed, 2014;Lee et. al., 2019).…”
Section: Resultsmentioning
confidence: 99%